TREND OF SPORTS TOURISM FOR SENIOR CITIZENS IN THAILAND - Chaimongkol, Maitree; Fugjaroen, Porratip (Academic Journal of Thailand National Sports University, 2024)
This research aimed to study the problems in sports tourism of Senior Citizens in Thailand, and to create and develop a sports tourism model for Senior Citizens in Thailand. The research was conducted by using future research methods with EDFR technique (Ethnographic Delphi Futures Research). Including 2 phases. First, Collection of qualitative data to be used as basic guidelines for frameworks of each element to Study problems in sports tourism of Senior Citizens in Thailand by using content analyses from in-depth interviews with 17 experts. Second, Collection of quantitative data through two rounds of Delphi technique to study possible elements and consensus among 17 experts. Using a five point rating scales questionnaire, the data were analyzed in terms of median, mode, and inter-quartile range. Problems in sports tourism for Senior Citizens in Thailand derived from qualitative data which was a trend that is expected to occur in the future the in-depth interview consisted findings showed 66 elements classified into 6 aspects. With a model that was the trend of Sports Tourism for Senior Citizens in Thailand showed 65 elements classified into 6 aspects. Those aspects were 1) attractions; 2) accessibility; 3) amenities; 4) available packages; 5) activities; and 6) ancillary services